Efficacy of Metacognitive Training for Patients With Schizophrenia in Psychiatric Emergency Wards: A Pilot Randomized Controlled Trial - Haga, Saori; Kobayashi, Masayoshi; Takehara, Ayako; Kawano, Kojiro; Endo, Kenji (Frontiers in Psychology, 2022)
Introduction: Metacognitive training (MCT) is a group program for improving cognitive bias in patients with schizophrenia. MCT has a reported positive effect on psychiatric symptoms and cognitive bias in patients with schizophrenia, but the effect of the intervention on patients with schizophrenia in the early recovery stage during hospitalization is not comprehensible. Therefore, this study aimed to investigate the efficacy of MCT in the early recovery stage of patients with schizophrenia in a Japanese emergency psychiatric ward. Method: This unblinded, pilot randomized controlled trial recruited 24 patients with schizophrenia aged 20–65 years. Patients were randomly divided into two groups: occupational therapy (OT) + MCT group and OT-only group. Using the two-way repeated-measures analysis of variance (ANOVA), changes in cognitive function, psychiatric symptoms, cognitive insight, and intrinsic motivation were compared between those at baseline and post-intervention and between the two groups. Furthermore, patient readmission during the year after discharge was compared between the groups. Results: The final analysis included eight patients in each group, owing to the withdrawal of some patients from the study. The two-way repeated-measures analysis of variance revealed significant differences in cognitive function in several domains within subjects. However, no significant differences between subjects were observed. Psychiatric symptoms showed significant within-subject improvement, and interaction was found for general psychopathology (p = 0.03). The variable of cognitive insight and self-reflectiveness was significantly different between subjects (p = 0.03). There was no significant difference in intrinsic motivation. Readmission within a year was significantly lower in the OT + MCT group than in the OT-only group (2 [25%] vs. 6 [75%]; p = 0.046). Conclusion: In a Japanese emergency psychiatric ward, this pilot randomized controlled study was the first attempt to investigate the efficacy of MCT in patients with schizophrenia suggesting that MCT may be effective in preventing psychiatric symptoms, poor cognitive insights, and readmissions. The study was registered in the University Hospital Medical Information Network Clinical Trials Registry (UMIN-CTR; UMIN000034106).